IMPLEMENTASI PENDEKATAN NEUROSAINS KOGNITIF DENGAN KONSEP JOYFUL LEARNING UNTUK MENINGKATKAN KEMAMPUAN LITERASI PADA SISWA KELAS V SEKOLAH DASAR - Dermawan Samosir, Elwin; Halimatusakkdiah; Abda’u Ansya, Yusron; Kibah Mandasari, Nur; Utami Humaira, Najwa; Rahma, Muthia (Universitas Negeri Medan, 2025)
Abstract: The purpose of this study was to improve students' literacy skills through the application of a cognitive neuroscience approach with the concept of joyful learning in class V of UPT SDN 106813 Amplas. The method used was Classroom Action Research (CAR) with two cycles, each consisting of planning, action, observation, evaluation, and reflection stages. The location of this study was at UPT SDN 106813 Amplas, with the subjects of the study being 30 fifth grade students who had difficulties in literacy skills. The results showed that in the first cycle, 65% of students managed to achieve scores above the Learning Objective Achievement Criteria (KKTP ≥70), with teacher activity reaching 78% and students reaching 70%. In the second cycle, after improving the learning strategy, 80% of students managed to achieve scores above the KKTP, with teacher activity reaching 90% and students increasing to 85%. The conclusion of this study is that the application of a cognitive neuroscience approach with the concept of joyful learning can improve students' literacy skills and their involvement in learning, so it is effective to be implemented in elementary schools. Keyword: Cognitive Neuroscience, Joyful Learning, Literacy, Elementary School Abstrak: Tujuan penelitian ini adalah untuk meningkatkan kemampuan literasi siswa melalui penerapan pendekatan neurosains kognitif dengan konsep joyful learning di kelas V UPT SDN 106813 Amplas. Metode yang digunakan adalah Penelitian Tindakan Kelas (PTK) dengan dua siklus, yang masing-masing terdiri dari tahap perencanaan, tindakan, observasi, evaluasi, dan refleksi. Lokasi penelitian ini adalah di UPT SDN 106813 Amplas, dengan subjek penelitian adalah 30 siswa kelas V yang mengalami kesulitan dalam kemampuan literasi. Hasil penelitian menunjukkan bahwa pada siklus pertama, 65% siswa berhasil mencapai nilai di atas Kriteria Ketercapaian Tujuan Pembelajaran (KKTP ≥70), dengan aktivitas guru mencapai 78% dan siswa mencapai 70%. Pada siklus kedua, setelah perbaikan strategi pembelajaran, 80% siswa berhasil mencapai nilai di atas KKTP, dengan aktivitas guru mencapai 90% dan siswa meningkat menjadi 85%. Kesimpulan dari penelitian ini adalah bahwa penerapan pendekatan neurosains kognitif dengan konsep joyful learning dapat meningkatkan kemampuan literasi siswa dan keterlibatan mereka dalam pembelajaran, sehingga efektif untuk diterapkan di sekolah dasar. Kata Kunci: Neurosain Kognitif, Joyful Learning, Literasi, Sekolah Dasar